In Silico Design and Evaluation of a Novel Multi-Epitope Vaccine Against Treponema denticola (strain ATCC 35405): A Reverse Vaccinology Approach (Community Based Medical Journal, 2025)
Treponema denticola is a gram-negative, drug resistant bacterium found in primary dentition infections and around teeth, causing inflammation and tissue homeostasis linked to periodontal diseases including early-onset periodontitis, necrotizing ulcerative gingivitis, and acute pericoronitis. In previous research, potential drug targets against the pathogen had been identified and characterized. However, as of now, there are no vaccines specifically available against T. denticola for human use. Hence, this study aims to design an immunoinformatic vaccine using a reverse vaccinology approach against this deadly pathogen. Human (HLA) allele specific potential T-cell and B-cell epitopes were shortlisted through a stringent procedure from a total of two antigenic proteins of T. denticola (namely, Acetate kinase AckA and Chromosomal replication initiator protein DnaA). The multi-epitope vaccine (MEV) was constructed using linkers with adjuvant human beta-defensin-3. The vaccine construct was verified, based on its antigenicity and physicochemical properties, and showed strong binding with the human receptor (TLR4). Molecular dynamics simulation confirmed the stable nature of the docked complex. The results of in silico immune simulation revealed that constructed vaccine activated B and T lymphocytes which induced high levels of antibodies and cytokines. Furthermore, in silico cloning analysis ensured efficient expression of desired gene in the microbial system. Thus, the vaccine construct developed in this study is capable of eliciting both innate and adaptive immunity and has all the potential for the development of a next-generation vaccine which may in turn effectively combat the periodontal pathogen T. denticola. Nevertheless, further in vitro and animal studies are warranted to strengthen our findings for its utility as a probable preventive measure.  CBMJ 2025 January: Vol. 14 No. 01 P: 139-155